Purification and Biochemical Characterisation of Rabbit Calicivirus RNA-Dependent RNA Polymerases and Identification of Non-Nucleoside Inhibitors - Nadya Urakova; Natalie Netzler; Andrew G. Kelly; Michael Frese; Peter A. White; Tanja Strive (Viruses, 2016)
Rabbit haemorrhagic disease virus (RHDV) is a calicivirus that causes acute infections in both domestic and wild European rabbits (Oryctolagus cuniculus). The virus causes significant economic losses in rabbit farming and reduces wild rabbit populations. The recent emergence of RHDV variants capable of overcoming immunity to other strains emphasises the need to develop universally effective antivirals to enable quick responses during outbreaks until new vaccines become available. The RNA-dependent RNA polymerase (RdRp) is a primary target for the development of such antiviral drugs. In this study, we used cell-free in vitro assays to examine the biochemical characteristics of two rabbit calicivirus RdRps and the effects of several antivirals that were previously identified as human norovirus RdRp inhibitors. The non-nucleoside inhibitor NIC02 was identified as a potential scaffold for further drug development against rabbit caliciviruses. Our experiments revealed an unusually high temperature optimum (between 40 and 45 °C) for RdRps derived from both a pathogenic and a non-pathogenic rabbit calicivirus, possibly demonstrating an adaptation to a host with a physiological body temperature of more than 38 °C. Interestingly, the in vitro polymerase activity of the non-pathogenic calicivirus RdRp was at least two times higher than that of the RdRp of the highly virulent RHDV.